l-Histidine-functionalized KIT-6 with embedded palladium nanoparticles as an efficient heterogeneous catalyst for oxidation of sulfide to sulfoxide and amination of aryl halides - Nafis Ahmad; Prakash Kanjariya; G. Padma Priya; Anjan Kumar; Rishabh Thakur; R. S. K. Sharma; Mukesh Kumari; Sharnjeet Kaur; Abhinav Kumar; Munther Kadheem (Scientific Reports)
Abstract Palladium nanoparticles were supported on L-H-functionalized KIT-6 (KIT-6@L-H-Pd) and evaluated using various characterization techniques such as TGA, FT-IR, SEM, XRD, EDS, and BET. KIT-6@L-H-Pd showed excellent catalytic performance as a recyclable nanocatalyst for the oxidation of sulfides to sulfoxides and the amination of aryl halides. This approach offers multiple benefits, including the use of readily available and cost-effective materials, a straightforward procedure, short reaction durations, high yields, and a catalyst that is easy to separate and reuse. Additionally, the catalyst can be recovered and reused multiple times without significant palladium loss or alteration in its activity.